Becoming 'Good Muslim' The Tablighi Jamaat in the UK and Bangladesh - Siddiqi, Bulbul (Springer Singapore, 2018)
The book uses an ethnographic approach to explore why the Tablighi Jamaat movement remains so successful in contemporary times. It shows that this success results from the positive image that it cultivates, and the systematic preaching activities of Tablighi Jamaat followers, and that the organisation's apolitical image, the public profile of the ijtema, the humbleness of Tablighi followers, and the attraction of belonging to the global Tablighi community all help to create a positive image of the Tablighi Jamaat among ordinary Muslims. The book also argues that the Tablighi Jamaat remains successful because of its ability to hold its followers within a Tablighi-guided life, which is perceived as protection against the Western lifestyle. Many elements of contemporary Western lifestyle are considered non-Islamic, and so by clearly defining what is Islamic and non-Islamic in modern society, the Tablighi Jamaat provides a way in which Muslims can live in the contemporary world, but remain good Muslims.